Challenges for sustainable urban mobility in small cities: study in Piratininga/SP - Silva, Vinicius Luis Arcangelo; Sigolo, Letícia Moreira (Scientific Journal ANAP, 2025)
Objective - This article seeks to identify and understand the barriers to the adoption of active modes of transport in urban travel in a small city with a population of less than 20,000 inhabitants.Methodology - The methodology adopted consists of a bibliographic review and the application of a questionnaire to a sample of the population according to the IBGE Census.Originality/relevance - The article also presents information on the profile of urban travel in a city with a population of less than 20,000 inhabitants (small-sized), which represents the majority of Brazilian municipalities. Most studies on this topic involve cities with a population of over 60,000 inhabitants, medium-sized cities and large centers, therefore, there is a gap in studies of sustainable urban mobility in small cities.Results - The results showed the predominance of automobile use in the municipality and some of the factors that influence this choice of mode of transport are related to flexibility of schedules, speed, easy access, safety (robbery), ease of travel and environmental comfort. Theoretical/methodological contributions – The literature review meets the conceptual needs of topics related to small cities and the adaptation of a specific questionnaire for this context. This review not only grounds the research in relevant theories, but also identifies gaps in existing knowledge, allowing for the development of more robust approaches. Adapting the questionnaire is a crucial step, as it considers the particularities and challenges faced by these cities, ensuring that the questions formulated are relevant and appropriate to the local reality. In this way, the theoretical and methodological contributions are intertwined, providing a solid framework for the analysis and interpretation of data, in addition to enabling a better understanding of the social and economic phenomena that permeate small urban centers.Social and environmental contributions – These data indicate that the local government has not effectively promoted the concept of sustainable urban mobility, thus being at odds with the guidelines of the country's current urban mobility policy. The results of this research can be used by municipal public managers to encourage the use of active modes of transport, especially for short journeys, and contribute to the development of a healthier city.
Keywords: Sustainable urban mobility; Small city; Healthy city